Simultaneous Analysis of Preservatives in Beverages Samples Using High Pressure Liquid Chromatography - Tetty Uli Oktaviana Situmeang; Jansen Silalahi; Hotnida Sinaga; Candra Sigalingging (Postgraduate, University of Mataram, 2025)
The development of ways to test the quantities of preservatives in beverages is required, since they are often included in these drinks. It is important to keep an eye on the amount of preservatives used in drinks since several research have shown that they may cause a variety of disorders. The researchers in this study set out to find out how much sodium benzoate and potassium sorbate were in various drinks sampled from the city of Medan. They also wanted to make sure their analytical approach was sound.This study used a reversed-phase HPLC technique using an Eclipse plus C18 column measuring 250 x 4.6 mm and 5 μm, a phosphate buffer mobile phase with a pH of 5, a 70:30 ratio of metanol, and a flow rate of 1.0 ml/minute. The linearity test passed with a coefficient of determination (R2) of 0.99998 - 0.99999, as shown in the method validation results. A range of 0.2541-0.31101 mg/kg was observed for the LOD values. There was an intermediate accuracy of 0.24% to 0.28%, a percent RSD of the repetability values ranging from 0.21% to 0.24%, and a LOQ from 0.8469 to 1,0338 mg/kg. An average of 99.95% to 104.52% recovery was the outcome. Beverage sweetener determination using the described approach has been a success.